2022
DOI: 10.1002/jctb.7281
|View full text |Cite
|
Sign up to set email alerts
|

Novelty in fossil fuel carbon abatement technologies in the 21st Century: post‐combustion carbon capture

Abstract: A global net zero target by mid-century and keeping the maximum global temperature rise to below 1.5 °C was agreed by nearly 200 nations at the 26th UN Climate Change Conference of the Parties. The Intergovernmental Panel on Climate Change advises that emission cuts by 45% are needed by 2030 in order to maintain the global temperature rise below the 1.5 °C target. To achieve this target, it is necessary to investigate technological options that are economically viable and globally acceptable for commercial dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 119 publications
0
8
0
Order By: Relevance
“…Postcombustion carbon capture (PCC) is the most mature CO 2 abatement option as demonstrated by commercial deployment projects such as the Petro Nova carbon capture and sequestration plant and the boundary dam carbon capture plant. 4 Many researchers have looked at different alternatives to improving the performance of conventional PCC to reduce the cost of its commercial deployment such as investigating different solvents, using plant configurations and process intensification 2,[5][6][7][8][9][10][11][12][13][14][15] Deployment of post-combustion carbon capture at a commercial scale must be cost-effective, since if it is costly, it will lead to increase in energy costs. Approaches to cutting capital and operating costs include process intensification options.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postcombustion carbon capture (PCC) is the most mature CO 2 abatement option as demonstrated by commercial deployment projects such as the Petro Nova carbon capture and sequestration plant and the boundary dam carbon capture plant. 4 Many researchers have looked at different alternatives to improving the performance of conventional PCC to reduce the cost of its commercial deployment such as investigating different solvents, using plant configurations and process intensification 2,[5][6][7][8][9][10][11][12][13][14][15] Deployment of post-combustion carbon capture at a commercial scale must be cost-effective, since if it is costly, it will lead to increase in energy costs. Approaches to cutting capital and operating costs include process intensification options.…”
Section: Introductionmentioning
confidence: 99%
“…The use of RPB for CO 2 capture was reported by many researchers and it found that RPB has the potential to boost mass transfer for the CO 2 capture process. 2,[10][11][12][13][14] Operating costs could easily be reduced by strategies such as intercooling and heat integration, among others. However, they reduce plant flexibility and make operation and control more difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon capture is an intriguing avenue for lowering net greenhouse gases emissions. Several methods exist for CO 2 capture, the most popular being postcombustion capture, where CO 2 is eliminated after combustion of fossil fuels. Capture is usually achieved using solvents such as amines, in either packed-bed columns or membrane contractors. , Enzymatic capture in membrane reactors is also a CO 2 removal method that has been investigated in recent years. , Precombustion capture, where fossil fuels are decarbonated before combustion, and oxycombustion, i.e., combustion under pure oxygen atmosphere, are also possible alternatives to postcombustion methods .…”
Section: Introductionmentioning
confidence: 99%
“…According to the findings of a number of researchers, shows that process intensification using rotating packed bed technology has the potential to cut down both capital and operational expenses [10][11][12][13]. Studies by Joel et al [12,14] demonstrated that there is a considerable reduction in size of around 12 times for the absorber and 9.63 times for the stripper when compared to conventional columns for CO2 capture.…”
Section: Introductionmentioning
confidence: 99%